A KAP study of oral health status among adults in a rural area of Jammu District - Bala, Kiran; Gupta, Reecha; Ara, Anjum; Sahni, Bhavna (International Journal Of Community Medicine And Public Health, 2018)
Background: Oral health is an integral part of general health and well being. It is important to know about the factors which having a bearing on oral health so that preventive measures can be taken. A research activity was planned to assess the oral health status and oral health practices of people in a rural community of Jammu region as very little is known about the knowledge and oral health practices of adults residing in this area. Methods: A cross sectional study for a period of four months was conducted in a village Tanda of R.S.Pura block of Jammu district. 324 adults above the age of 20 years (145 males and 179 females) were interviewed face to face with the help of a questionnaire consisting of questions from WHO technique of self assessment of oral health along with some more questions exploring the knowledge, attitude and local oral health practices. Results: The overall results showed adequate knowledge but poor attitude regarding oral health. Out of 324 subjects studied, 41.7% paid dental visits on having pain in teeth, gums or mouth and only 3.0% visited dentist routinely. 85.6 % of participants reported using brush and toothpaste but only 24.0% of all respondents brushed twice a day and only 16.7% of the respondents changed their tooth brush within three months. Conclusions: Oral health awareness, by promoting community based programs should be undertaken at periodic intervals for better oral health and hygiene.